(3aJM GdNHjQ GddWja aj TQM fXe GdJQUja aj Yde GdJUQjas - (3EHQGgje Hf eMeO GdHGLhQis; (3YHO GdQMef Hf YjSi Hf eQTO, CHh GdhLGgI GdYeQj GdeQTOj,J (B1037 (3g` s
(3ChdgG (B:s
(3ajbhd GdYHO GdabjQ hJPcQI Chdi GdCdHGH Ydi GdefXheI GdeSeGI HGdJQUja ai Yde GdJUQja s
(3BNQgG (B:s
(3hGdYah ef Tje GdSGOGJ eCehd hGdMeO ddg QH GdYGdejf s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B321 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B164s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B161 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B181s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdUQas